1985
DOI: 10.1039/c39850000494
|View full text |Cite
|
Sign up to set email alerts
|

17O n.m.r. studies of enol and phenol compounds with intramolecular hydrogen bonds

Abstract: The natural abundance 40.67 MHz 1 7 0 n.m.r. spectra of enol and phenol (naphthol) compounds with intramolecular hydrogen bonds are reported and the chemical shifts of the chelated hydroxy groups are assigned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…13,14,17 The 17O signal for the CxO oxygen of a,b-unsaturated ketones.13,18 appears at ca. 530 ppm and for that of enaminones at ca.…”
Section: Methodsmentioning
confidence: 99%
“…13,14,17 The 17O signal for the CxO oxygen of a,b-unsaturated ketones.13,18 appears at ca. 530 ppm and for that of enaminones at ca.…”
Section: Methodsmentioning
confidence: 99%
“…29 Although in the course of this work the temperature and solvent in 15 N NMR experiments were always the same, the relative contributions of the ketimine and enaminone forms were not constant owing to their strong dependence on substituents. 13 C NMR spectra (see Table 2) also allow one to distinguish between different tautomers. In general, δ 13 C values increase (downfield effect) when R becomes more electron accepting for C11 and C12 in the ketimine and for C2 in the enaminone forms.…”
Section: Nmr Spectra Of Tautomeric Mixturesmentioning
confidence: 99%
“…[9][10][11] Various NMR techniques have been used to study the conformation and configuration of enaminones. 7-9,11- 13 Similarly, multinuclear magnetic resonance spectroscopic techniques have provided an excellent tool to investigate tautomeric equilibria quantitatively. 4,14, 15 It has been reported that protonationcaused chemical shifts of the ring nitrogen atom in aza aromatic compounds are very large.…”
Section: Introductionmentioning
confidence: 99%
“…There are continuous studies which have appeared on the title compounds, due to the diverse properties of these compounds, i.e., spectroscopic studies (Vargas et al, 1985;Lapachev et al, 1985;Razniewska-Lazecka et al, 1986), studies concerning their biological activity such as bacterial, fungicidal or spermicidal (Khorana et al, 1967;Sharma et al, 1980;Wang et al, 1990), or their use as starting materials for the preparation of Schiff base compounds which are frequently used as ligands for complexing transition metals (MacDonald et al, 1982;Fern~.ndez-G. et al, 1987;Elerman et al, 1991). However, there have been no reports, to our knowledge, on the single crystal X-ray diffraction study of compounds I or II.…”
Section: Introductionmentioning
confidence: 99%